Drinking Water Quality Assessment Using Water Quality Index in Ado-Ekiti and Environs, Nigeria - Busayo Mutiat Olowe; Jacob O. Oluyege; Oladiran Famurewa (Challenges and Advances in Chemical Science Vol. 1, 2021)
Water quality is a description of chemical, physical and biological characteristics of water in connection with intended use(s) and a set of standards. The quality of water sources has been deteriorated due to point source and non-point source pollution. Therefore, the water quality of any specific source can be investigated using physical, chemical and/or microbiological parameters. One of the most effective tools in communicating information on the quality of water is by using the term water quality index (WQI), which is a rating, reflecting the composite influence of different water quality parameters. WQI provides a single number that expresses the overall water quality at a certain location and time based on several water quality parameters. Hence, this study aimed to assess the quality of drinking water sources in Ado-Ekiti and environs, Nigeria, using Water Quality Index (WQI). This study was carried out using experimental study design at the Department of Microbiology, Ekiti State University, Ado-Ekiti, Ekiti State, Nigeria, between January 2014 and August 2014. Among several formulated water quality indices, the study adopted the Weighted Arithmetic Water Quality Index (WAWQI) method, which classifies water quality according to the degree of purity. The WAWQI was determined on the basis of various physico-chemical parameters which included pH, total dissolved solids, turbidity, total hardness, calcium, magnesium, sulphate, chloride and nitrate. The parameters were determined using standard methods. The results of the study showed that the mean values of the physico-chemical parameters of majority of the samples fell below the WHO maximum permissible limits while others were above WHO specifications. The calculated WAWQI revealed the water quality level of the different water sources as follows; 54.16, 65.12, 67.46, 56.29, 46.08 and 49.59 for borehole, stream, pipe-borne, well, spring and packaged water samples, respectively. This result is an indication that the analyzed water samples from different sources were of poor water quality with the exception of spring and packaged water samples which are of good quality in terms of physico-chemical qualities and thus safe for human consumption.